Outstanding optical properties of thermally grown (Bi2Se3)1-x (Bi2Te3)x thin films. (1st June 2022) - Adam, A.M.; Diab, A.K.; Tolan, Mohamed; El-Qahtani, Z.M.H.; Refaat, A.A.; El-Hadek, Medhat A.; Elsehly, E.M.; El-Khouly, A.; Alharbi, Abdulaziz N.; Khovaylo, V.; Ataalla, M.
Abstract: Thin layers of (Bi2 Se3 )1-x (Bi2 Te3 )x samples were prepared by vacuum thermal evaporation technique. Starting materials are bulk alloys of good crystallinity. Characterization and optical properties of the synthesized films are discussed. Structure properties, surface features and roughness of the deposited films are probed via XRD, SEM and HRTEM techniques, which confirmed perfect crystallinity and nano-scalability of the samples. Transmission and reflection spectra attested that all prepared films have a growing transparency upon increasing the wavelength beyond the infra-red region, with optical band gap energy varies between 0.72 and 0.91 eV. Interesting absorption is detected in the visible light region. Enhancement of light transmission in layered bismuth chalcogenides is achieved through incorporation of Bi2 Te3 into the (Bi2 Se3 )1-x (Bi2 Te3 )x system at x = 0.20. A maximum transmittance of 81.5% was observed in the IR region. The concerned materials showed high interest for transparent and highly conductive electrodes and also for flexible electronic devices.